Reflections on the Transformation of the World Order: Emerging Trends and Impending Perspectives - Khojayan, Karine (Journal of Political Science: Bulletin of Yerevan University, 2022)
The article analyzes the latest trends of the started process of transformation of world order, trying to explain it by various concepts, bringing forward by researchers and scientists, substantiating for many decades the urgent need for the existence of a dominant state - a hegemon which plays a role of a stabilizer of the international relations. The article focuses on the concept of hegemonic stability, arguing that existence of hegemon especially in the political and economic system is a necessary condition for maintaining global peace and stability. Special attention is paid to the conditions that contribute to the decline of hegemony. Drawing parallels between today’s realities and the concepts, highlighted by Charles Kindleberger, Robert Gilpin, Immanuel Wallerstein and other researchers, the article proves that even based on the concepts of the mentioned researchers who for many years justified the “stabilizing role” of the US hegemony, after the global fanatical crisis of 2008 a new phase of development is becoming more and more noticeable. Referring to the point of view of I. Wallerstein, the article concludes that even maintaining dominance to a certain extent in a number of areas, such as military, political, the unipolar world order has already gone down in history.